Migraine is a dysfunction of neuronal potassium ion channels - M., Girishwaran; Lulu, S. Sajitha (Frontiers in Neurology, 2025)
Migraine is a primary headache disorder characterized by unilateral pain usually with aura, that affects approximately one in six individuals in India. The underlying biomechanical processes of migraine are still poorly understood, and new research is constantly being published. One of the major factors in migraine pathogenesis is the dysfunction of ion channels in the trigeminal nuclei and sensory cortices. Potassium channels are modulators and regulators of neuronal signaling and conductance, playing an important role in maintenance of the membrane potential and neuronal conduction. Therefore, potassium channel dysfunctions are potential factors in migraine pathogenesis, and thus targets for specific antimigraine prophylaxis. This review reveals that potassium channels play a significant role in pathogenesis and management of migraine. Dysfunctions in KATP channels, K2P channels including TRESK and TREK-1, small and large conductance calcium-sensitive potassium channels (SKCa and BKCa), and voltage-gated potassium channels (KV) are known to affect the incidence and progression of migraine in the general populace. KATP openers can induce migraine like phenotype, but KATP blockers have so far not been effective in reducing the intensity of migraine headache. Potassium channels are a potential druggable target for migraine prophylaxis with several compounds currently in preclinical trials.